Veterinarian–pharmacist collaboration in veterinary medicine: Roles, practices, and perceptions—A scoping review - Dan Kambayashi; Shota Suzuki; Masayoshi Hirohara (PLoS ONE, 2026)
Background Pharmacists are expanding their participation in veterinary healthcare teams and assuming roles beyond traditional dispensing duties. However, the scope of these collaborative practices and the degree of mutual recognition vary substantially across regions. Objectives This scoping review aimed to organize the existing literature on collaboration between veterinarians and pharmacists, clarifying current roles, practical applications, and professional perceptions within the veterinary field. Methods A scoping review was conducted to examine the roles, practices, and perceptions associated with veterinarian–pharmacist collaboration in veterinary medicine and related fields. Two researchers independently searched PubMed, Web of Science, the Cochrane Library, and Ichushi-Web, and additionally screened Google Scholar to identify gray literature (from database inception to August 2025, in English or Japanese). Records were independently screened at the title/abstract and full-text levels using predefined eligibility criteria, and relevant studies were identified. Results The search yielded 239 records, of which 16 studies published between 2007 and 2024 were included. Studies were conducted primarily in the United States (n = 7), New Zealand (n = 3), and Japan (n = 3); one study collected data from both Japan and Taiwan. Most studies employed cross-sectional survey designs. Pharmacist roles most frequently involved compounding and dispensing for animal patients (62.5%), followed by drug information (DI) and consultation (37.5%), inventory and supply management (25.0%), client education (18.8%), and safety and exposure control (12.5%). Conclusions This scoping review demonstrates that veterinarian–pharmacist collaboration is described within a limited and regionally variable evidence base, with pharmacists most often contributing through compounding/dispensing and drug information support. Sustained and scalable implementation will require improved mutual understanding of professional roles, strengthened veterinary-specific education for pharmacists, and more robust empirical research to inform collaborative practice models.